2022
DOI: 10.1212/wnl.0000000000200035
|View full text |Cite|
|
Sign up to set email alerts
|

Association of CSF, Plasma, and Imaging Markers of Neurodegeneration With Clinical Progression in People With Subjective Cognitive Decline

Abstract: Background and ObjectivesMultiple biomarkers have been suggested to measure neurodegeneration (N) in the AT(N) framework, leading to inconsistencies between studies. We investigated the association of 5 N biomarkers with clinical progression and cognitive decline in individuals with subjective cognitive decline (SCD).MethodsWe included individuals with SCD from the Amsterdam Dementia Cohort and SCIENCe project, a longitudinal cohort study (follow-up 4±3 years). We used the following N biomarkers: CSF total (t)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
46
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 52 publications
5
46
2
Order By: Relevance
“…And second, that tau PET is known to not be sensitive to early tau pathology, which may have decreased the power to detect these associations in previous studies. 5052 On the other hand, recent studies have shown the association between higher levels of plasma GFAP and increased risk of clinical progression and steeper rates of cognitive decline (even after adjusting for amyloid), 5355 which supports a link with tau pathology given the known strong association between tau and clinical symptoms. Thus, our hypothesis is that plasma GFAP may be associated with AD pathology, but it may primarily relate to early deposited tau tangles.…”
Section: Discussionmentioning
confidence: 92%
“…And second, that tau PET is known to not be sensitive to early tau pathology, which may have decreased the power to detect these associations in previous studies. 5052 On the other hand, recent studies have shown the association between higher levels of plasma GFAP and increased risk of clinical progression and steeper rates of cognitive decline (even after adjusting for amyloid), 5355 which supports a link with tau pathology given the known strong association between tau and clinical symptoms. Thus, our hypothesis is that plasma GFAP may be associated with AD pathology, but it may primarily relate to early deposited tau tangles.…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, this effect was more pronounced for plasma GFAP than plasma NfL. This could be explained by the fact, that GFAP seems to be a marker of the earliest AD pathology with an association between GFAP levels and amyloid load, while NfL could be more useful in terms of disease monitoring and progression (Verberk et al, 2021 ; Ebenau et al, 2022 ). Unfortunately, for discriminating the disease states of MCI and AD, none of the three biomarker-based panels could add a significant benefit to the age+sex+ APOE4 panel.…”
Section: Discussionmentioning
confidence: 99%
“…Neurofilament light and VILIP-1 are biomarkers of neurodegeneration and have been shown to have prognostic value for progression in patients with MCI or dementia due to AD [ 81 , 87 ]. GFAP, a marker of astrogliosis, predicts decline in those with subjective cognitive impairment [ 88 ]. Tau PET offers prognostic information and forecasts MCI and AD dementia progression [ 89 , 90 ].…”
Section: Biomarker Definition and Classificationmentioning
confidence: 99%